2005
DOI: 10.1063/1.1898224
|View full text |Cite
|
Sign up to set email alerts
|

Global optimization of bimetallic cluster structures. II. Size-matched Ag-Pd, Ag-Au, and Pd-Pt systems

Abstract: Genetic algorithm global optimization of Ag-Pd, Ag-Au, and Pd-Pt clusters is performed. The 34- and 38-atom clusters are optimized for all compositions. The atom-atom interactions are modeled by a semiempirical potential. All three systems are characterized by a small size mismatch and a weak tendency of the larger atoms to segregate at the surface of the smaller ones. As a result, the global minimum structures exhibit a larger mixing than in Ag-Cu and Ag-Ni clusters. Polyicosahedral structures present general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
157
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(171 citation statements)
references
References 11 publications
10
157
0
4
Order By: Relevance
“…[1][2][3] Previous studies of bimetallic clusters such as Ag-Pd, Au-Pd, and Ag-Cu systems revealed that the different atomic size and surface energy between the two metal components cause preferential surface segregation of the component having relatively large size and low surface energy. [3][4][5][6] In general, the other element segregates into the cluster core, forming an overall coreshell cluster structure. [4][5][6] In spite of recent remarkable development in chemical synthesis methods [7][8][9][10][11][12] and the technical importance of bimetallic clusters, there have been few studies on the formation mechanism and structure of bimetallic clusters.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3] Previous studies of bimetallic clusters such as Ag-Pd, Au-Pd, and Ag-Cu systems revealed that the different atomic size and surface energy between the two metal components cause preferential surface segregation of the component having relatively large size and low surface energy. [3][4][5][6] In general, the other element segregates into the cluster core, forming an overall coreshell cluster structure. [4][5][6] In spite of recent remarkable development in chemical synthesis methods [7][8][9][10][11][12] and the technical importance of bimetallic clusters, there have been few studies on the formation mechanism and structure of bimetallic clusters.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] In general, the other element segregates into the cluster core, forming an overall coreshell cluster structure. [4][5][6] In spite of recent remarkable development in chemical synthesis methods [7][8][9][10][11][12] and the technical importance of bimetallic clusters, there have been few studies on the formation mechanism and structure of bimetallic clusters. Current computational research has been mainly oriented to the physical properties of single component metal clusters 13) or surface segregation and reaction of bimetallic surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational simulations for predicting cluster properties have been regarded as powerful tools relative to the experimental difficulties. For example, Genetic Algorithms (GA) 16,17 and basin hopping (BH) [18][19][20] have shown to be reasonably accurate and are widely used for inspecting the global minimum of various empirical PEFs. 21 As alternative methods, minima hopping (MH) for complex molecular systems 22 and simulated annealing (SA) for closed-shell systems 23 have also been employed.…”
Section: Introductionmentioning
confidence: 99%